Widespread genome duplications throughout the history of flowering plants - Cui, Liying; Wall, P. Kerr; Leebens-Mack, James H.; Lindsay, Bruce G.; Soltis, Douglas E.; Doyle, Jeff J.; Soltis, Pamela S.; Carlson, John E.; Arumuganathan, Kathiravetpilla; Barakat, Abdelali; Albert, Victor A.; Ma, Hong; et al. (Genome Research, 2006)
Genomic comparisons provide evidence for ancient genome-wide duplications in a diverse array of animals and plants. We developed a birth–death model to identify evidence for genome duplication in EST data, and applied a mixture model to estimate the age distribution of paralogous pairs identified in EST sets for species representing the basal-most extant flowering plant lineages. We found evidence for episodes of ancient genome-wide duplications in the basal angiosperm lineages including Nuphar advena (yellow water lily: Nymphaeaceae) and the magnoliids Persea americana (avocado: Lauraceae), Liriodendron tulipifera (tulip poplar: Magnoliaceae), and Saruma henryi (Aristolochiaceae). In addition, we detected independent genome duplications in the basal eudicot Eschscholzia californica (California poppy: Papaveraceae) and the basal monocot Acorus americanus (Acoraceae), both of which were distinct from duplications documented for ancestral grass (Poaceae) and core eudicot lineages. Among gymnosperms, we found equivocal evidence for ancient polyploidy in Welwitschia mirabilis (Gnetales) and no evidence for polyploidy in pine, although gymnosperms generally have much larger genomes than the angiosperms investigated. Cross-species sequence divergence estimates suggest that synonymous substitution rates in the basal angiosperms are less than half those previously reported for core eudicots and members of Poaceae. These lower substitution rates permit inference of older duplication events. We hypothesize that evidence of an ancient duplication observed in the Nuphar data may represent a genome duplication in the common ancestor of all or most extant angiosperms, except Amborella.
10.1101/gr.4825606